Ultrasonic renal size and its correlates among diabetic outpatients at Jimma University Medical Center, Southwest Ethiopia - Diliab Desta, M.Sc; Mesfin Zewdu, M.Sc; Almaz Ayalew, M.Sc; Tilahun Alemayehu Nigatu, M.Sc (Elsevier, 2020)
Background: The kidney size of diabetic patients is valuable outcome parameter for evaluating health status of kidneys and progression of disease. This study investigated the effect of diabetes on ultrasonic kidney size among diabetic patients at Chronic Diseases Clinic and Radiology Department of Jimma University Medical Center (JUMC). Ethiopia. The hypothesis was that the magnitude of ultrasonic renal dimensions would change with duration of diabetes and glycemic level. Methods: Hospital-based prospective study was conducted from June 26 to August 26, 2018 at Chronic Diseases Clinic and Radiology Department of JUMC. Participants were diabetic patients on regular follow-up and recruited consecutively on voluntary bases. Ultrasound was used to measure renal dimensions (length, width and thickness) by a senior radiologist. Patients' heights and weights were also measured and used to calculate body mass index. Moreover, sex, age and records of diabetes type, diabetic duration, fasting blood sugar and blood pressure were retrieved. Descriptive statistics, Pearson correlation, t-tests and multiple linear regressions were carried out using SPSS to identify independent predictors of renal dimensions. Results: Two-hundred and four adult diabetic outpatients consented for participation and underwent ultrasonic examination. From these, 29 patients were excluded due to evidence of morphological anomalies in one or both of their kidneys. As a result 175 participants (95 male and 80 female) aged between 20 and 80 years were included in this analysis. The right kidney length ranged from 8.00 to 12.40 cm (mean = 10.26), while that of the left kidney was between 8.80 and 13.00 cm (mean = 10.42). Mean volume of the right and left kidneys were 98.5 (±23.2) and 105.4 (±23.6) cm3, respectively. These measurements were not significantly different between men and women. The right kidney length modestly correlated negatively with age (r = −0.131, p = 0.034), and positively with body weight (r = 0.368, p = 0.000), height (r = 0.215, p = 0.005) and BMI (r = 0.312, p = 0.000). Likewise, the left kidney length was positively correlated with weight (r = 0.309, p = 0.000), height (r = 0.176, p = 0.020), BMI (r = 0.270, p = 0.000) and DBP (r = 0.155, p = 0.042). Age, body height and BMI were identified as independent predictors of renal length on both sides, while height and BMI predict renal volume irrespective of age in both kidneys. Conclusions: The renal size dimensions obtained in this study are comparable with renal biometry reported for different population. Body size variables were found determinants of ultrasonic renal size, while diabetes related variables show non-significant association. The current results should be validated through further studies.